Suppression of cytomegalovirus-specific CD8+T cells by everolimus. Issue 5 (May 2014) - Jin, Nan; Malcherek, Georg; Mani, Jiju; Zurleit, Romy; Schmitt, Anita; Chen, Baoan; Freund, Mathias; Ho, Anthony D.; Schmitt, Michael
Abstract Everolimus (RAD-001) has recently been used as an immunosuppressive drug to treat patients after hematopoietic stem cell transplant (HSCT), thereby reducing cyclosporine-related nephrotoxicity. We studied the immunomodulatory effect of everolimus on mitogen-stimulated and particularly cytomegalovirus (CMV)-specific cytotoxic T cells. Proliferation of CD4+ and CD8+ T cells stimulated with staphylococcal endotoxin B and phytohemagglutinin was strongly inhibited at very low doses. Proliferation of CMV-specific CD8+ T cells could be completely suppressed. Similarly, the frequency of CMV-specific, cytokine-secreting and CD137-expressing CD8+ T cells decreased in a dose-dependent manner. However, interferon-γ (IFN-γ) secretion by CMV-specific CD8+ T cells remained unchanged, as could be demonstrated by intracellular cytokine staining. As reactivation of CMV plays a pivotal role in the outcome of patients after HSCT, attention must be paid to early detection and preemptive treatment of CMV reactivity in patients treated with everolimus.